KELAYAKAN BUDIDAYA BANDENG SISTEM KERAMBA JARING TANCAP DESA API-API KECAMATAN WONOKERTO KABUPATEN PEKALONGAN - Novindra Novindra; Zaynal Arifin (Jurusan Agribisnis, Fakultas Pertanian, Perikanan dan Biologi Universitas Bangka Belitung, 2023)
Api-Api Village has potential fishery resources, especially milkfish cultivation, but milkfish cultivation has obstacles and challenges due to sea tidal disasters and other things. Farmers continue to exploit the existing potential by cultivating the stepped net cage system. The objectives of this research were (1) to determine the general condition of brackish water ponds in Api-Api village and (2) to analyze the financial feasibility of cultivating milkfish using the stepped net cage system. The data collection method used was direct interviews with 30 farmers. The analytical tool used is financial feasibility analysis (NPV, Net B/C, IRR, PP). The results of the financial feasibility analysis show an NPV value of Rp. 71,838,127, Net B/C of 1.64, IRR of 15.33% and Payback Period of 2 years seven months 17 days. Therefore, cultivating milkfish using the KJT system in Api-Api Village is feasible.